The Chilean Health System: 20 Years of Reforms - Manuel Annick (Instituto Nacional de Salud Pública, 2002)
The Chilean health care system has been intensively reformed in the past 20 years. Reforms under the Pinochet government (1973-1990) aimed mainly at the decentralization of the system and the development of a private sector. Decentralization involved both a deconcentration process and the devolution of primary health care to municipalities. The democratic governments after 1990 chose to preserve the core organization but introduced reforms intended to correct the system's failures and to increase both efficiency and equity. The present article briefly explains the current organization of the Chilean health care system. It also reviews the different reforms introduced in the past 20 years, from the Pinochet regime to the democratic governments. Finally, a brief discussion describes the strengths and weaknesses of the system, as well as the challenges it currently faces.